Closing chapters urban change, religious reform, and the decline of Youngstown's Catholic elementary schools, 1960-2006 - Welsh, Thomas G., 1961- (Lanham : Lexington Books, 2011)
Closing Chapters attempts to explain the disintegration of urban parochial schools in Youngstown, Ohio, a onetime industrial center that lost all but one of its eighteen Catholic parochial elementary schools between 1960 and 2006. Through the examination of Youngstown, Welsh sheds light on a significant national phenomenon: the fragmentation of American Catholic identity.
Cover; Half title; Title; Copyright; Contents; Acknowledgments; Dedication; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Epilogue; Bibliography; Addendum; Index.
Description based on print version record.
Keywords: Catholic elementary schools -- Ohio -- Youngstown -- History; Catholics -- Religious identity -- United States; Urban education -- Ohio -- Youngstown -- History; Education; EDUCATION / Elementary; Catholic elementary schools -- Ohio -- Youngstown -- History; Education, Urban -- Ohio -- Youngstown -- History; Catholics -- Religious identity -- United States; Electronic books